2001
DOI: 10.1042/bj3560571
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of the human annexin A5 gene promoter: a downstream DNA element and an upstream long terminal repeat regulate transcription

Abstract: Human annexin A5 is a ubiquitous protein implicated in diverse signal transduction processes associated with cell growth and differentiation, and its gene regulation is an important component of this function. Promoter transcriptional activity was determined for a wide 5′ portion of the human annexin A5 gene, from bp −1275 to +79 relative to the most 5′ of several discrete transcription start points. Transfection experiments carried out in HeLa cells identified the segment from bp −202 to +79 as the minimal pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…It has been reported that the ANXA5 variants can affect RPL risks (12). In addition, in a study of 70 RPL cases, the promoter and coding sequences of ANXA5 showed various mutations, including the loss of prothrombin G20210A mutation (10).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the ANXA5 variants can affect RPL risks (12). In addition, in a study of 70 RPL cases, the promoter and coding sequences of ANXA5 showed various mutations, including the loss of prothrombin G20210A mutation (10).…”
Section: Introductionmentioning
confidence: 99%